Urban design, public space and the dynamics of creative milieus: a photographic approach to Bairro Alto (Lisboa), Gracia (Barcelona) and Vila Madalena (São Paulo) - Costa, P. (2013)
Drawing on some results of a broader research project, this paper aims to discuss the relation between urban design and the creative dynamics in cultural districts. Appropriation and production of public spaces in three “creative quarters” (Bairro Alto, Lisbon; La Gracia, Barcelona; Vila Madalena, São Paulo) are analyzed. The specific conditions and ambiances which seem to be determinant to embed sustainable creative processes in these areas are studied, aiming to explain the development of “creative milieus” and their relation with the urban socioeconomic and morphological dimensions. The main conceptual and empirical framework of the project is briefly presented, in order to sum up the main key-issues on the relation between urban form and creative clustering. Then, the methodological and empirical approach followed in this particular part of our work is described. The analysis and discussion of more than one thousand images allowed characterizing each district on 15 analytical dimensions, covering material aspects, human appropriation and livability and the symbolic dimensions of it. Departing from a discussion on the boundaries of public spaces and their relevance for creative dynamics (through the conviviality and sociability they promote), it is argued that urban design characteristics and specific place morphologies are determinant for the attractiveness of creative activities and for the appropriation of these areas. Their role on the sustainability of each of these districts, as they become challenged as “vibrant” and “creative” centers in their cities, is also discussed. Finally some concluding policy guidelines are drawn out from the analysis.